2013
DOI: 10.1002/pd.4274
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmune fetal hydrops and lysosomal storage disease: the finding of vacuolated lymphocytes in ascitic fluid in two cases

Abstract: What's already known about this topic? Nonimmune fetal hydrops (NIFH) is a heterogeneous condition and establishing a diagnosis can be challenging. Inborn errors of metabolism are one of many possible etiologies for NIFH. Inborn errors of metabolism are often missed in utero. What does this study add? We present two cases of NIFH caused by underlying lysosomal storage disease: galactosialidosis and mucopolysaccharidosis type VII. The unique finding of vacuolated lymphocytes in fetal peritoneal fluid lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…Dugan et al have reported a lower proportion of VLs in early pregnancy . Interestingly, in our cohort, the proportion of VLs was not correlated with gestational age.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Dugan et al have reported a lower proportion of VLs in early pregnancy . Interestingly, in our cohort, the proportion of VLs was not correlated with gestational age.…”
Section: Discussioncontrasting
confidence: 72%
“…Their morphological features may vary greatly, especially with regard to vacuole size and number, and the presence of granules of different colors . The presence of VLs in fetal ascites of fetuses with LSD may constitute an indication for LSD testing . We sought to describe the cytological features of VLs in fetal effusions and to determine the utility of VLs for the prenatal diagnosis of LSDs in the setting of fetal effusions.…”
Section: Introductionmentioning
confidence: 99%
“…in a large series of cases of nonimmune hydrops fetalis . In addition, the presence of vacuolated cells suggests a metabolic storage disease . We observed this in ten cases of our cases, for which five different metabolic storage diseases were observed.…”
Section: Discussionsupporting
confidence: 71%
“…The presence of such cells in peripheral blood smears has been described after birth in several LSDs, such as GM1 gangliosidosis, ISSD, sialidosis, mucolipidosis type II, MPS VII, and Wolman disease (Anderson et al 2005). Recently, the presence of vacuolated cells in fetal ascites fluid has been observed in fetuses affected by various LSDs (Dugan et al 2014;Dreuxetal.2015). Two classes of plasmatic biomarkers, oxysterols [cholestane-3β, 5α,6 β-triol, and 7-ketocholesterol (Jiang et al 2011;Pagan et al 2015)] and lysosphingolipids [lysophingomyelin and isoform 509 (Chuang et al 2014;Giese et al 2015;Pettazzoni et al 2015a)], have recently emerged for diagnosing Niemann-Pick disease types C and A/B (sphingomyelinase deficiency).…”
Section: Lysosomal Storage Disorders (Lsds)mentioning
confidence: 98%